STUDI KASUS PADA SISWA DENGAN LOW SELF-ESTEEM DI SMP NEGERI 2 KOTA PONTIANAK - Rian; Yuline; Amallia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low self-esteem is a psychological problem characterized by negative self-evaluation and low self-confidence that may hinder students’ academic, social, and emotional development. This study aims to describe the characteristics, causal factors, impacts, and intervention process of Low self-esteem through individual counseling services. The research employed action research with a case study design involving two eighth-grade students of SMP Negeri 2 Kota Pontianak. Data were collected through interviews, observations, and documentation. The results showed that both subjects experienced social withdrawal, low self-confidence, and negative self-perceptions influenced by social anxiety, negative thinking patterns, low self-efficacy, and parenting factors. Intervention using a behavioral approach with positive reinforcement, shaping, and homework techniques conducted biweekly resulted in more adaptive behaviors and increased self-confidence. These findings highlight the importance of behavioral-based individual counseling as an effective strategy to improve students’ self-esteem and support their psychological development in school settings.